2021
DOI: 10.3390/ma14133536
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Behavior of Carbon-Based Nanomaterial-Reinforced Nickel Metal Matrix Composites

Abstract: Carbon nanotubes (CNTs) and graphene nanoplatelets (GNPs) with exceptional mechanical, thermal, chemical, and electrical properties are enticing reinforcements for fabricating lightweight, high-strength, and wear-resistant metal matrix composites with superior mechanical and tribological performance. Nickel–carbon nanotube composite (Ni-CNT) and nickel–graphene nanoplatelet composite (Ni-GNP) were fabricated via mechanical milling followed by the spark plasma sintering (SPS) technique. The Ni-CNT/GNP composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 85 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…The Nickel-GO nanocomposite coatings on the SS440 samples were prepared using pulse electrodeposition (PED). The tribological results revealed that the GO particles improved the friction and wear resistance through the formation of a tribolayer at the contact interface [117]. Studies on Ni-graphene composite coatings showed that COFs of the composite coatings were reduced by increasing the amount of graphene reinforcement which caused improvement in wear resistance properties (Figure 7) [105], [106].…”
Section: Tribological Propertiesmentioning
confidence: 98%
“…The Nickel-GO nanocomposite coatings on the SS440 samples were prepared using pulse electrodeposition (PED). The tribological results revealed that the GO particles improved the friction and wear resistance through the formation of a tribolayer at the contact interface [117]. Studies on Ni-graphene composite coatings showed that COFs of the composite coatings were reduced by increasing the amount of graphene reinforcement which caused improvement in wear resistance properties (Figure 7) [105], [106].…”
Section: Tribological Propertiesmentioning
confidence: 98%
“…Therefore, diamonds have been extensively studied for applications in electronic devices [15], thermal management, diffractive optical elements [16], and biomedicine [17]. In most applications, carbon nanomaterials are grown on substrates, such as silicon carbide, graphite, platinum, and nickel [18][19][20]. Existing evidence suggests that the heterostructure of graphene and diamond is beneficial for many applications.…”
Section: Introductionmentioning
confidence: 99%
“…The main challenges during stir casting processing are obtaining a homogeneous distribution of CNTs and forming a stable interface between CNTs and Al. 28,29 These problems can be rectified using magnesium as a wetting agent and an ultrasonic probe stirrer to break down the clusters of MWCNTs. 30 Zhou et al 31 examined the tribological properties of CNTs/Al composites at a load of 30 N and 0.1571 m/s sliding speed.…”
Section: Introductionmentioning
confidence: 99%